Pretreatment method of nano probe sample
By using neutral anhydrous abrasive liquid for sample polishing and surfactant plasma combined cleaning, the problems of uneven and hollow surfaces of nanoprobe samples were solved, efficient pretreatment of samples was achieved, and the accuracy of electrical testing was improved sex.
Patent Information
- Application Number
- CN202310967449.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the pretreatment method of nanoprobe samples cannot effectively solve the problem of unevenness and hollowness of the sample surface, resulting in poor contact between the probe and the sample, affecting the accuracy of electrical properties measurement.
The sample is polished with neutral anhydrous abrasive liquid to prevent the target structure material from being corroded faster under chemical reactions and mechanical grinding, and ensure the flatness of the sample surface. At the same time, the cleaning process is performed using a combination of surfactant and plasma to remove residual substances and prevent the production of surface carbon.
Through this method, a nanoprobe sample with a flat surface without holes and clean surface was obtained, which improved the efficiency of electrical properties and the accuracy of results.
Smart Images

Figure CN119437826A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor test sample preparation, and in particular to a nanoprobe sample pre-treatment method. Background Art
[0002] Nanoprobe is a commonly used electrical failure analysis machine. By using scanning electron microscope imaging, it can perform electrical measurements on specified devices at the nanoscale. For samples with single bit failure, it is often necessary to grind the sample to the contact hole layer first, and use the nanoprobe to measure the electrical curve of each transistor in the failed bit. After locating the failed transistor, physical property analysis can be performed. Nanoprobes have certain requirements for samples. On the one hand, the sample must be highly clean to prevent carbon accumulation on the sample surface due to long-term scanning with a scanning electron microscope, resulting in poor contact between the probe and the sample and affecting electrical measurement; on the other hand, the contact hole surface must be flat to facilitate stable landing of the probe.
[0003] For samples that have been ground to, for example, the contact hole layer, two pre-treatment methods are usually used: deionized water rinsing or water polishing.
[0004] (1) Deionized water rinse
[0005] Mechanical grinding is affected by the material selection ratio. Due to the different grinding rates between the contact hole metal (such as tungsten) and the surrounding oxide, the metal tungsten contact hole will eventually bulge after grinding. Deionized water rinsing cannot make the sample surface flat, and the probe will easily slip off after piercing the raised tungsten surface. In addition, samples that are only rinsed with deionized water are often not clean enough, and after being bombarded by the electron beam of the scanning electron microscope, carbon is easily accumulated on the surface, affecting detection.
[0006] (2) Water throwing
[0007] The dual effects of chemical reaction and mechanical grinding during chemical mechanical grinding of samples will cause contact holes to be empty, resulting in poor contact between the probe and the sample, and inaccurate electrical measurement results. The main mechanism is that metal tungsten will undergo oxidation corrosion reaction in alkaline solution to generate oxides, which will further react to generate soluble salt ions WO4 2- ,Right now
[0008] W+6OH - →WO3+3H2O
[0009] WO3+2OH - →WO4 2- +H2O
[0010] Applying mechanical grinding at the same time as the chemical reaction will cause the reaction products to be removed faster, speeding up the chemical reaction in the direction of the products, and ultimately leading to the occurrence of contact hole voids.
[0011] The above problems cause damage to the nanoprobe sample. Therefore, it is necessary to provide a pretreatment method for the nanoprobe sample to solve the above problems in the prior art. Summary of the invention
[0012] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a method for pre-treating a nanoprobe sample.
[0013] To achieve the above object, the technical solution of the present invention is as follows:
[0014] A nanoprobe sample pretreatment method, comprising:
[0015] providing a sample having a target layer, the target layer containing a heterogeneous target structure;
[0016] Grind the sample to the target layer using a first physical grinding method, so that the target structure is exposed from the sample surface;
[0017] Grinding the sample surface by a second physical grinding method until the roughness reaches a standard;
[0018] Using a first cleaning method to treat the sample surface to remove residual substances on the sample surface;
[0019] The surface of the sample is treated by a second cleaning method to prevent carbon deposition on the surface of the sample.
[0020] Furthermore, the first physical grinding method includes grinding the sample using a neutral water-based grinding liquid.
[0021] Furthermore, during the process of grinding the sample using the first physical grinding method, the morphology of the sample surface is observed using a first observation method, and / or, after the sample surface is treated using the second cleaning method, the morphology of the sample surface is observed using a second observation method.
[0022] Furthermore, the neutral water-based polishing liquid includes a neutral water-based silica polishing liquid.
[0023] Furthermore, the second physical grinding method includes polishing the sample surface using a neutral anhydrous grinding liquid.
[0024] Furthermore, the neutral anhydrous polishing liquid includes an organic solvent-based polishing liquid.
[0025] Furthermore, the first cleaning method includes cleaning the sample surface with a surfactant and then rinsing with deionized water.
[0026] Furthermore, the surfactant includes a water-based weakly alkaline treatment liquid.
[0027] Furthermore, the second cleaning method includes using plasma to clean the sample surface.
[0028] Furthermore, the first observation method includes observing the flatness of the sample surface under an optical microscope, and confirming the position of the target structure by comparing with the layout until the target layer is polished and the target structure is exposed from the sample surface; the second observation method includes using a scanning electron microscope and observing the cleanliness of the sample surface using a backscattering mode under low acceleration voltage conditions until it is confirmed that the sample surface is clean and the target structure is in a full state.
[0029] It can be seen from the above technical scheme that the present invention can prevent the target structure material (such as the metal material (such as tungsten) of the target structure such as the contact hole or through hole) from accelerating corrosion under the action of chemical reaction and mechanical grinding by using a neutral anhydrous grinding liquid to prepare the sample, which can effectively avoid the problem of voids in the target structure and ensure the flatness of the sample surface. At the same time, by using a combination of surfactants and plasma to clean the surface of the sample after grinding, the cleanliness of the sample surface can be guaranteed, and the problem of carbon accumulation on the surface of the sample caused by electron beam bombardment during testing can be prevented. Therefore, the method of the present invention can obtain a nanoprobe sample with a flat surface, no voids and cleanness, thereby improving the efficiency of electrical testing and the accuracy of test results. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Flow chart of a nanoprobe sample pretreatment method according to an embodiment of the present invention. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0032] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0033] refer to Figure 1 , Figure 1 FIG. 1 is a flow chart of a method for pre-treating a nanoprobe sample according to an embodiment of the present invention. Figure 1 As shown, a nanoprobe sample pretreatment method of the present invention comprises the following steps:
[0034] Step S1: providing a sample having a target layer, wherein the target layer contains a heterogeneous target structure.
[0035] In some embodiments of the present invention, the sample includes a substrate, a front-end device (such as a gate structure, etc.) disposed on the substrate, one or more interlayer dielectric layers disposed on the substrate, a metal interconnection layer disposed in the interlayer dielectric layer, and a contact hole in the interlayer dielectric layer connected between the front-end device and the metal interconnection layer. The contact hole is filled with a metal material, such as tungsten. The interlayer dielectric layer where the contact hole is located is a contact hole layer, i.e., a target layer defined in the present invention. The contact hole material is different from the interlayer dielectric layer material, i.e., a heterogeneous target structure defined in the present invention.
[0036] It can be understood that any device structure on the sample that has a material different from the layer in which it is located (such as the interlayer dielectric layer), such as a through hole, etc., the layer in which it is located can be used as the target layer of the present invention, and the device structure with different materials in the target layer can be used as the target structure of the present invention.
[0037] Step S2: grinding the sample to a target layer using a first physical grinding method, so that the target structure is exposed from the sample surface.
[0038] In some embodiments of the present invention, the first physical grinding method includes grinding the sample using a neutral water-based grinding liquid.
[0039] In some embodiments of the present invention, the neutral water-based polishing liquid includes a neutral water-based silica polishing liquid (commercial polishing liquid).
[0040] In some embodiments of the present invention, according to step S2, a manual grinder and a silicon dioxide grinding liquid are used to grind and remove layers from the sample, starting from the metal interconnect layer until the top of the contact hole layer is exposed.
[0041] Step S3: Grind the sample surface using a second physical grinding method until the roughness meets the standard.
[0042] In some embodiments of the present invention, the second physical grinding method includes polishing the sample surface using a neutral anhydrous grinding liquid.
[0043] In some embodiments of the present invention, the neutral anhydrous polishing liquid includes an organic solvent-based polishing liquid.
[0044] In some embodiments of the present invention, the organic solvent-based polishing liquid includes anhydrous ethanol, which is safe and non-toxic, can be used with confidence, and is easy to obtain, thereby improving efficiency.
[0045] In some embodiments of the present invention, according to step S3, deionized water is turned on, and the grinding liquid on the grinding pad is cleaned with a scraper. In order to avoid the reaction between deionized water and the contact hole metal (such as tungsten), the sample is treated under the action of a safe and non-toxic organic solvent. Use anhydrous ethanol commonly used in laboratories, first pour a certain amount of anhydrous ethanol (such as 20-50ml) on the grinding pad, and set a certain speed (such as 200-300 revolutions per minute), and add anhydrous ethanol to the grinding pad with a washing bottle while grinding, so that the sample is in anhydrous ethanol environment. At the same time, the residual silica particles on the grinding pad can also be used to increase the polishing effect. Polish in this way for a certain time (such as 1-2 minutes). Thereby, the surface of the sample where the contact hole layer is located is ground to a roughness that meets the standard, and a sample with a smooth surface and no voids is obtained, which is conducive to the stable landing of the probe.
[0046] Step S4: using a first cleaning method to treat the surface of the sample to remove residual substances on the surface of the sample.
[0047] In some embodiments of the present invention, the first cleaning method includes cleaning the sample surface with a surfactant and then rinsing with deionized water.
[0048] In some embodiments of the present invention, the surfactant includes a water-based weakly alkaline treatment solution.
[0049] In some embodiments of the present invention, the water-based weakly alkaline treatment solution includes soapy water.
[0050] In some embodiments of the present invention, according to step S4, the polished sample is placed on the stage, and finger cots are put on, and the surface of the sample is gently wiped for 1-2 minutes using a test paper soaked in soapy water to remove residual substances on the surface of the sample. The sample is then rinsed with deionized water for 1-2 minutes, and then the sample is completely blown dry with an air gun.
[0051] Step S5: using a second cleaning method to treat the surface of the sample to prevent carbon deposition on the surface of the sample.
[0052] In some embodiments of the present invention, the second cleaning method includes cleaning the sample surface using plasma.
[0053] In some embodiments of the present invention, according to step S5, the sample processed in step S4 is placed in a plasma cleaning machine using a fixture, and the surface of the sample is cleaned for 5-10 minutes using plasma. The surface active components of the sample are further removed by the reaction of the plasma, which can effectively reduce the carbon deposition caused by the electron beam bombarding hydrocarbons. Thus, a sample with high surface cleanliness is obtained, which is conducive to good contact between the probe and the sample and is conducive to electrical measurement.
[0054] In some embodiments of the present invention, during the process of grinding the sample using the first physical grinding method, the morphology of the sample surface is observed using a first observation method, and / or, after the sample surface is treated using the second cleaning method, the morphology of the sample surface is observed using a second observation method.
[0055] In some embodiments of the present invention, the first observation method includes observing the flatness of the sample surface under an optical microscope, and confirming the position of the target structure by comparing with the layout, until the target layer is polished and the target structure is exposed from the sample surface; the second observation method includes using a scanning electron microscope and observing the cleanliness of the sample surface using a backscattering mode under low acceleration voltage (e.g., 0.7 kV) until it is confirmed that the sample surface is clean and the target structure is in a full state. Then, the transistor electrical curve is measured with a nanoprobe, and the sample is prepared by a focused ion beam and photographed by a transmission electron microscope according to the results of the electrical analysis.
[0056] Using a scanning electron microscope to observe the surface morphology of the sample treated by the above method of the present invention, it can be seen that the contact holes are full and there are no obvious voids. The electrical curve of the sample was measured using a nanoprobe, and there was no obvious carbon deposit on the surface of the sample after the test. From the test results, the electrical curve of the transistor is smooth and the source and drain are symmetrical, which also shows that the nanoprobe is in good contact with the sample. It can also be seen from the perspective electron microscope photos of the cross-section samples prepared by the focused ion beam that the surface of the improved polished sample is flat.
[0057] In summary, the present invention uses a neutral anhydrous grinding liquid to prepare samples, which can prevent the target structure material (such as the metal material (such as tungsten) of the target structure such as the contact hole or through hole) from accelerating corrosion under the action of chemical reaction and mechanical grinding, and can effectively avoid the problem of voids in the target structure, and ensure the flatness of the sample surface. At the same time, by using a combination of surfactants and plasma to clean the surface of the sample after grinding, the cleanliness of the sample surface can be guaranteed, and the problem of carbon accumulation on the surface of the sample caused by electron beam bombardment during testing can be prevented. Therefore, the method of the present invention can obtain a nanoprobe sample with a flat surface, no voids and cleanness, thereby improving the efficiency of electrical testing and the accuracy of test results.
[0058] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for pre-treating a nanoprobe sample, characterized in that: include: providing a sample having a target layer, the target layer containing a heterogeneous target structure; Grind the sample to the target layer using a first physical grinding method, so that the target structure is exposed from the sample surface; Grinding the sample surface by a second physical grinding method until the roughness reaches a standard; Using a first cleaning method to treat the sample surface to remove residual substances on the sample surface; The surface of the sample is treated by a second cleaning method to prevent carbon deposition on the surface of the sample.
2. The method for pre-treating a nanoprobe sample according to claim 1, characterized in that: The first physical grinding method includes grinding the sample using a neutral water-based grinding liquid.
3. The method for pre-treating a nanoprobe sample according to claim 1, characterized in that: During the process of grinding the sample using the first physical grinding method, the morphology of the sample surface is observed using a first observation method, and / or, after the sample surface is treated using the second cleaning method, the morphology of the sample surface is observed using a second observation method.
4. The method for pre-treating a nanoprobe sample according to claim 2, characterized in that: The neutral water-based polishing liquid includes a neutral water-based silicon dioxide polishing liquid.
5. The method for pre-treating a nanoprobe sample according to claim 1, characterized in that: The second physical grinding method includes polishing the sample surface using a neutral anhydrous grinding liquid.
6. The method for pre-treating a nanoprobe sample according to claim 5, characterized in that: The neutral anhydrous polishing liquid includes an organic solvent-based polishing liquid.
7. The method for pre-treating a nanoprobe sample according to claim 1, characterized in that: The first cleaning method includes cleaning the sample surface with a surfactant and then rinsing with deionized water.
8. The method for pre-treating a nanoprobe sample according to claim 7, characterized in that: The 5 surfactants include a water-based weakly alkaline treatment solution.
9. The method for pre-treating a nanoprobe sample according to claim 1, characterized in that: The second cleaning method includes cleaning the sample surface using plasma.
10. The method for pre-treating a nanoprobe sample according to claim 3, characterized in that: The first observation method includes observing the flatness of the sample surface under an optical microscope, and confirming the position of the target structure on the 0-photographed plate until the target layer is polished and the target structure is exposed from the sample surface; the second observation method includes using a scanning electron microscope and observing the cleanliness of the sample surface using a backscattering mode under low acceleration voltage conditions until it is confirmed that the sample surface is clean and the target structure is in a full state.